AB0069 Strong age-dependent effects of dopamine on joint invasion in arthritis. (15th June 2017) - Nie, L Van; Rehart, S; Neumann, E; Müller-Ladner, U; Capellino, S
Abstract : Background: Preventing synovial fibroblasts (SF) from migrating into the adjacent cartilage is a desirable therapeutic target in rheumatoid arthritis (RA) in order to avoid joint destruction and disability. In our previous studies we could show that RASF as well as SF from osteoarthritis (OA) patients express all dopamine receptor (DR) subtypes and dopamine stimulation alters pro-inflammatory cytokines ( Capellino S et al, A&R 2014 ). Objectives: Therefore, we aimed to elucidate a potential dopamine-mediated impact on joint invasion and destruction in arthritis. Methods: SF from RA and OA patients were obtained from patients undergoing knee joint replacement surgery (mean age: 74.3±11.3yrs at OA and 73.7±10.3 yrs at RA patients) to investigate dopamine receptor (DR)-distribution within the RA synovium and in the invasion zone, immunohistochemistry was performed for all five DR-subtypes. Migration and motility assays were performed under D1-like (D1DR and D5DR) and D2-like (D2DR, D3DR and D4DR) receptor stimulation. Dopamine effects on MMP3 and proMMP1 were evaluated using ELISA. Results: D1DR, D4DR and D5DR were found to be stronger expressed close to the invasion zone and more cells were expressing the respective DR. Migration of RASF and OASF was significantly correlated with patients' age at surgery: younger patients (≤75years) showed an increase in migration up to 78% whereas older patients (≥75years) showed a reduced migration of up to 50% (OA n=8; RA n=7). There was no difference between RA and OA patients and between D1-like and D2-like receptor stimulation. The same effect could be observed in the motility assay (OA n=5; RA n=6). MMP3 levels are altered under DR activation (OA n=6; RA n=6). Conclusions: The high DR expression close to the invasion zone suggests a direct role of dopamine on RASF aggressiveness and may contribute to cartilage invasion. This was confirmed in the in vitro assays, and supports the idea of a therapeutic potential of the dopamine pathway in RA. Disclosure of Interest: None declared